Biogas effluent treatment by Landoltia punctata for starch biomass production - Kirdponpattara, Suchata; Kittiwongwattana, Chokchai; Phisalaphong, Muenduen; Chanroj, Salil; Sriariyanun, Malinee (My University, 2023)
Due to the high potential of using Landoltia punctata in biogas effluent treatment and starch accumulation, three integrated processes were proposed: (1) bioethanol production from duckweed, (2) biogas production from vinasse, and (3) biogas effluent treatment with sequentially increasing starch-rich duckweed biomass. This recent work focuses only on the third process, which involves the treatment of wastewater from biogas effluent and the production of L. punctata with high starch content. L. punctata showed a significantly higher TKN removal and biomass production than Lemna aequinoctialis. After nine days of wastewater treatment and five days of starch accumulation, L. punctata grew by 4.3 g/m2/day, with 44.4% starch content. NH3, NH4+, and PO43− in the biogas effluent were rapidly utilized in the first three days for L. punctata's growth. The upregulation of AGPase genes in the starch biosynthesis pathway was observed when the environmental conditions changed in both nutrient starvation and population reduction. Production of starch-rich L. punctata using biogas effluent is a sustainable feedstock for the bioethanol process. Moreover, L. punctata-based stabilization pond is a promising technique for biogas effluent treatment.
Keywords: Biogas effluent; Duckweed; Landoltia punctata; Phytoremediation; Starch accumulation; Wastewater treatment